6-7 ЁШЛИ БОЛАЛАРДА САКРОВЧАНЛИК ҚОБИЛИЯТИНИ РИВОЖЛАНТИРИШ - Абдуллаев, Б.Б.; Хайтметов, И.С.; Халилов, У.Б. (SCIENCE and SOCIETY, 2023)
The article deals with the development of such an important skill as jumping in children 5-6 years old through various gymnastic exercises.